THE USE OF STORY TELLING IN PAIRED TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILL - Subono, Denis Wijayadi (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This research was aimed at improving the students’ speaking skill through Paired Story Telling technique. This research analyzed how the procedure of the use of Paired Story Telling technique to improve the students’ speaking skill, whether the use of Paired Story Telling technique could improve the students’ speaking skill, and how far the implementation of the students’ speaking skill of students of the first grade of Junior High School level. through Paired Story Telling technique. Forty students of the first grade of Junior High School level. were instructed through Paired Story Telling technique to improve their speaking skill. The methodology of this research used Classroom Action Research (CAR). There were two cycles to give the students more opportunities to improve their understanding about how to speak English with confident in front of the class and comprehend the passage well and effectively in pairs. This technique could help the students remember about storytelling and the details of the narrative text. In the implementation of Paired Story Telling technique, the students could enrich their vocabularies, grammar, pronunciation and be confident to speak English in front of the class. Based on the results, the research recommends using Paired Story Telling technique in speaking skill.